2018
DOI: 10.3389/fmicb.2018.01323
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Arsenic Alters the Microbiome of Larval Zebrafish

Abstract: Exposure to environmental toxins such as heavy metals can perturb the development and stability of microbial communities associated with human or animal hosts. Widespread arsenic contamination in rivers and riparian habitats therefore presents environmental and health concerns for populations living near sources of contamination. To investigate how arsenic affects host microbiomes, we sequenced and characterized the microbiomes of twenty larval zebrafish exposed to three concentrations of arsenic that are foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 88 publications
1
37
1
Order By: Relevance
“…In the functional context, a pioneering rumenbased study found fermentation rates were inhibited~30% by the addition of~30 μM As(III) to rumen microflora enrichments; levels of As(III) required to inhibit fermentation were less than that toxic to the animal itself (Forsberg, 1978). In a phylogenetic context, studies examining insects, fish, rodents and ruminants (Schramm et al, 2003;Pass et al, 2015;Dahan et al, 2018;Gaulke et al, 2018;Liu et al, 2018;Xue et al, 2019b) are congruent in illustrating that arsenic alters the microbiome community composition. Changes corresponded to increases in Bacteroidetes and decreases of Firmicutes.…”
Section: Arsenic Perturbation Of the Microbiomementioning
confidence: 99%
“…In the functional context, a pioneering rumenbased study found fermentation rates were inhibited~30% by the addition of~30 μM As(III) to rumen microflora enrichments; levels of As(III) required to inhibit fermentation were less than that toxic to the animal itself (Forsberg, 1978). In a phylogenetic context, studies examining insects, fish, rodents and ruminants (Schramm et al, 2003;Pass et al, 2015;Dahan et al, 2018;Gaulke et al, 2018;Liu et al, 2018;Xue et al, 2019b) are congruent in illustrating that arsenic alters the microbiome community composition. Changes corresponded to increases in Bacteroidetes and decreases of Firmicutes.…”
Section: Arsenic Perturbation Of the Microbiomementioning
confidence: 99%
“…This protocol revealed that 131 I-PEG-AuNRs are extraordinary stable in vivo condition. In a recent work, cyclic arginine-glycine-aspartate acid (RGD)-conjugated gold nanoparticles were used to follow integrins in high resolution by means of cryo-electron tomography: it is possible to localize AuNPs in cells and identify the precise interactors within cells [115,116]. This development is a clear example of the AuNPs use of structural cell biology.…”
Section: Aunrsmentioning
confidence: 99%
“…We extracted and purified microbial DNA from 200 mL of filtered water (0.22 µm Sterivex filter) while using the PowerWater kit from MO BIO laboratories (Mo Bio, Carlsbad, CA, USA). Microbiomes were then characterized via the targeted gene amplification of the 16S rRNA V4 region, as described elsewhere [28]. Following gel-purification, the libraries were pooled at equimolar ratios and sequenced on the MiSeq Illumina platform adapted for 250-bp paired-end reads (Wright Labs, Juniata College, Huntingdon, PA, USA).…”
Section: Dna Extraction and Sequencingmentioning
confidence: 99%
“…Patterns of diversity within the ASV tables, only including ASVs that appeared at least three times and that were present in at least 10% of the samples, were analyzed using a modified version of the pipeline that was described in Dahan et al [28] and implemented in R version 3.2.3 (R scripts are available upon request). Supplemental File 1 provides a mapping file linking the sample names and the relevant metadata and Supplemental File 2 provides a full description of the statistical and visualization analyses.…”
Section: Processing and Visualization Of 16s Rrna Sequence Datamentioning
confidence: 99%